PREDICTING OUTCOMES AFTER ACUTE MYOCARDIAL INFARCTION: ECHOCARDIOGRAPHIC ANALYSIS OF LEFT VENTRICULAR VOLUMES AND EJECTION FRACTION - Shamsutdinova Guzel Baxodirovna; Eshtemirova Dildoraxon Ulugbek qizi (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2025)
Acute myocardial infarction (AMI) represents a serious health concern due to its significant impact on subsequent cardiac function and patient prognosis. The left ventricular (LV) volumes and ejection fraction (EF) serve as key clinical markers in guiding patient management. This study aimed to assess post-AMI left ventricular remodeling using echocardiographic parameters and to predict both short- and long-term outcomes in patients. A total of 120 AMI patients were prospectively analyzed over a 6-month follow-up period. Demographic data, sex, and major risk factors (hypertension, diabetes, dyslipidemia) were recorded. Echocardiographic measurements of baseline and 6-month LV end-diastolic volume (EDV), end-systolic volume (ESV), and EF were obtained. The data were analyzed in relation to LV remodeling and the development of chronic heart failure. Results demonstrated that patients with elevated baseline EDV and ESV had significantly reduced EF and were at increased risk of long-term heart failure and mortality. Furthermore, an EF below 40% was identified as an independent predictor of poor prognosis. These findings highlight the importance of echocardiographic assessment in guiding individualized monitoring and optimizing therapeutic strategies in AMI patients. In conclusion, EDV, ESV, and EF measured by echocardiography are effective tools for predicting post-AMI LV remodeling and identifying high-risk patients.